Beneficial Newborn Care Practices in Rural Eastern Uganda : a Cross-sectional Study. - Owor, Michael O.; Murokora, Daniel; Wanyenze, Rhoda K.; Waiswa, Peter; Matovu, Joseph K. B. (METHODS, 2014)
This was a cross-sectional study conducted among 1,616 mothers who had delivered 28 in the past year in two districts (Luuka & Buyende) in Eastern Uganda. Data collection took 29 place between September and November 2011. Data were collected on socio-demographic and 30 economic characteristics (ie household possessions, fuel material used for lighting and cooking, 31 and animals owned), health facility attendance, skilled delivery attendance, number of children 32 ever born, distance to health facility and early newborn care knowledge and practices. 33 Descriptive statistics were computed to determine the proportion of mothers who used beneficial 34 newborn care practices (optimal thermal care; good feeding practices; weighing and immunizing 35 the baby immediately after birth; and good chord care) during the neonatal period and conducted 36 multivariable logistic regression to assess the predictors of use of all beneficial newborn care 37 practices. Analysis was done using STATA statistical software, version 12.1. 38 39 Results: Of the 1,616 mothers enrolled, 773 (38.4%) were aged 25-34; 1,472 (91.1%) were 40 married; 326 (20.2%) had secondary or more education; while 1,357 (84%) were laborers or 41 peasants. Uptake of any beneficial newborn care practices was 13.2% overall; lower in Luuka 42 (11%, n= 797) than in Buyende (15.3%, n= 819). Immunization (80.7% in Luuka; 82.5% in 43 Buyende) and weighing the baby after birth (68% Luuka; 58.9% Buyende) were the most 44 prevalent newborn care practices reported by mothers. At the multivariable analysis, number of 45 ANC attendances (3-4 vs. 1-2: OR= 1.40, 95% CI= 1.04, 1.89), skilled delivery vs. unskilled 46 delivery: OR= 2.69, 95% CI= 1.99, 3.64), husband’s education status (Primary vs. no education: 47 OR= 0.66, 95% CI= 0.48, 0.89), and socio-economic status (middle vs. low: OR= 1.48, 48 95% CI= 1.05, 2.08) were significant predictors of utilization of any beneficial newborn care 49 practices among mothers. 50